Carcass characteristics and meat quality of lambs fed diets with different roughage: concentrate ratios supplemented with liquid residue of cassava - Adriana Guim (Acta Scientiarum. Animal Sciences, 2023)
The objective of this study was to evaluate the effects of lambs fed two roughage: concentrate (R:C) ratios, with or without the liquid residue of cassava (LRC) on carcass traits and meat quantity. Forty lambs (19.5 ± 1.45 kg body weight), non-castrated, crossbred Santa Inês were distributed in a completely randomized 2 × 2 factorial design. There was no effect (p > 0.05) of the inclusion of LRC on the variables. The roughage:concentrate ratio of 40:60 promoted higher values for empty body weight, hot carcass weight, cold carcass weight, subcutaneous thickness fat, cooling loss,Longissimusmuscle area, carcass morphometric measurements, and commercial cuts. Higher weight of leg, muscles, fat, bone and other tissues, as well as for the ratio muscle:fat, and muscle:bone was observed in lambs fed 40R:60C. For the meat chemical composition, there was the effect (p < 0.05) only for ether extract (EE) for lambs fed 40R:60C ratio. The redness (a*) of meat was greater (p < 0.05) for lambs fed 80R:20C. The other physicochemical characteristics were not influenced. The roughage:concentrate ratio of 40:60 improves the carcass traits and commercial cuts, but does not promote changes in meat quality, independent of supplementation with liquid residue of cassava.